One-year results of half-dose versus one-third-dose photodynamic therapy in chronic or recurrent central serous chorioretinopathy - Jirarattanasopa Pichai; Banchasakjaroen Vanchalerm; Ratanasukon Mansing (BMC Ophthalmology, 2021)
Abstract Background Central serous chorioretinopathy (CSC) is characterized by an accumulation of subretinal fluid (SRF) in the macula. It is usually treated by laser photocoagulation or photodynamic therapy (PDT) with consisting of different doses and power. This study aimed to compare the efficacy of half-dose PDT and one-third-dose PDT in chronic or recurrent CSC. Methods A retrospective review of patients with chronic or recurrent CSC who were treated with either a half-dose or one-third-dose PDT, and had follow up 12 months afterwards. Best-corrected visual acuity (BCVA), central retinal thickness (CRT) and resolution of subretinal fluid (SRF) at baseline as well as 1, 3, 6 and 12 months post-PDT were assessed. Results Forty-six eyes and 20 eyes received half-dose and one-third-dose PDT, respectively. The study showed efficacy of the one-third-dose PDT compared with half-dose PDT in BCVA improvement (0.10±0.04 logMAR for one-third-dose versus 0.17±0.04, for half-dose, P=0.148) and CRT improvement (125.6±24.6 μm for one-third-dose versus 139.1±16.54, for half-dose, P=0.933) at 12 months. The SRF recurrence rate was significantly higher in the one-third-dose PDT group compared with the half-dose PDT group (40.0% versus 15.2%, P=0.027) at 12-months. Conclusion At 12 months, the one-third-dose PDT was effective in terms of BCVA and CRT improvement, when compared with half-dose PDT. However, this study showed that one-third-dose PDT had a higher recurrence rate of SRF.